DIABETES MEDICATIONS AS MONOTHERAPY OR METFORMIN - BASED COMBINATION THERAPY FOR TYPE 2 DIABETES : A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Early combination therapy may reduce glucotoxicity. This method may improve insulin sensitivity and preserve bulk and function.10 Early combination therapy with several antihypertensive agents may increase costs and patient compliance due to the number of pills, but a fixed-dose medication combination can help.The aim: This article compared monotherapy or metformin - based combination therapy for type 2 diabetes medicationsMethods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 88 articles, whereas the results of our search on SagePub brought up 56 articles. The results of the search conducted for the last year of 2013 yielded a total 42 articles for PubMed and 31 articles for SagePub. In the end, we compiled a total of 11 papers, 7 of which came from PubMed and four of which came from SagePub. We included three research that met the criteria. Conclusion: Initiation of the AHA combination of metformin and other drugs may provide better results in diabetes control. In addition, the combination of two and three drugs did not show significantly different results.